Critical Breakdown of Discourse Categories in Relation to (Preschool) Teacher's Oral Performance - Petek Tomaž (University of Maribor Press, 2013)
The discussion presents an attempt of a critical breakdown of discourse categories in relation to the (preschool) teacher's oral performance in class and during activities related to school or kindergarten. We established that during the educational process, (preschool) teachers find themselves in different situations and circumstances of oral performances. Since they use discourses in their communication rather than individual sentences or even words, they must, among other things, be familiar with the characteristics of different discourse categories in order to be efficient. When researching the discourse categories we have, in compliance with different scientific definitions, somewhat modified the Toporišič Žagar classification in accordance with communication methods and functional varieties and limited ourselves to the discourse categories that are directly or indirectly related to a (preschool) teacher's oral performance in class. During the discussion, we focused on whether the (preschool) teacher already starts his or her oral performance when entering the classroom and whether at least a part of class is an oral performance.